Molecular epidemiology of entamoeba : First description of Entamoeba moshkovskii in a rural area from central Colombia (2015)
Background Entamoeba histolytica, E. dispar and E. moshkovskii are the most frequent species described in human infection where E. histolytica is the only true pathogen. The epidemiology of this infection is complex due to the absence of a routine exam that allows a correct discrimination of the Entamoeba species complex. Therefore, molecular methods appear as the unique epidemiological tool to accomplish the species discrimination. Herein, we conducted a cross-sectional study to determine the frequency of Entamoeba species infections in a group of asymptomatic individuals from a rural area in central Colombia. Methodology/Principal Findings A total of 181 fecal samples from asymptomatic children under 16 years old from the hamlet La Vírgen, Cundinamarca (Colombia) that voluntarily accepted to participate in the study were collected. The fecal samples were examined by light microscopy and DNA-extracted, subsequently submitted to molecular discrimination of E. dispar/E. histolytica/E. moshkovskii infection based on a multiplex PCR assay targeting the 18S rRNA fragment. To confirm the species description, twenty samples were randomly submitted to DNA sequencing of the aforementioned fragment. By direct microscopic examination, frequency of the complex E. histolytica/E. dispar/E. moshkovskii was 18.8%(34/181). PCR showed a frequency of 49.1% (89/181), discriminated as 23.2%(42/181) that were positive for E. dispar, 25.4% (46/181) for E. moshkovskii and 0.55% (1/ 181) for E. histolytica. Also, mixed infections were detected between E. dispar and E. moshkovskii at 4.42% (8/181) of the samples. Molecular barcoding confirmed the diagnosis depicted by the multiplex PCR assay. Conclusions/Significance This is the first description of E. moshkovskii in Colombia and the second report in South- America to our knowledge. Our results suggest the need to unravel the true epidemiology of Entamoeba infections around the world, including the real pathogenic role that E. moshkovskii may have. Copyright: © 2015 López et al.This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.